Chemical variables influencing microbial properties in composted tannery sludge-treated soil - Araujo, A. S. F.; Santos, V. M.; Miranda, A. R. L.; Nunes, L. A. P. L.; Dias, C. T. S.; Melo, W. J. de [UNESP] (Springer, 2018)
Repeated applications of composted tannery sludge to arable soils have the potential to greatly alter soil chemistry and thus potentially influence the soil microbial community over time. This study performed multivariate analyses using the data of soil microbial biomass, respiration, and enzymes activities obtained during 5 years (2010-2014) in a long-term experiment with composted tannery sludge amendment. The correlation between the soil microbial and chemical properties, via the analysis of similarity matrices, revealed calcium as the main single factor influencing the microbial properties, in 2010 and 2011. Afterward, chromium was the most important chemical variables driving the microbial properties in 2012, 2013, and 2014. The non-metric multidimensional scaling demonstrated that the soil microbial properties changed with composted tannery sludge application from 2010 to 2014. Multivariate analysis from soil microbial data with composted tannery sludge amendment, during 5 years, showed calcium and chromium as being the most significant variables influencing the soil microbial properties in composted tannery sludge-treated soil.
Keywords: Wastes; Microbial properties; Microbial activity; Soil biochemistry